Home Ownership and Household Portfolio Choice - Thomas Michielsen; Remco Mocking; Sander van Veldhuizen (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the effect of home equity and indebtedness on financial portfolio choices of Dutch households during the period 2006-2012. Using a large administrative dataset at the household level we estimate how home equity and the outstanding mortgage amount influence the share of liquid assets held in stocks. We apply different econometric methods to take selection and endogeneity into account. In our preferred specifications both home equity and the household's amount of mortgage debt have a non-significant impact on the risky asset share.
Keywords: G11; D14; R31; 330; portfolio choice; house price shocks